Respon Publik Terhadap Kasus Seunghan RIIZE: Analisis Reputasi SM Entertainment Melalui Komentar Netizen di Platform Digital - Adriana Airlia Yusrin; Maya May Syarah; Herman Herman (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
The case involving Seunghan from RIIZE drew widespread attention on social media, particularly on platform X, and triggered various public responses toward SM Entertainment. This study aims to analyze public perceptions of SM Entertainment's reputation through netizen comments on digital platforms. Employing a qualitative approach and participatory observation method, the research examines 15 viral posts made by netizens related to the case. Findings reveal that public opinion is significantly shaped by the pseudo-environment formed on social media. Criticism of SM’s crisis management, disappointment among the fandom, and allegations of supporting bullying emerged as dominant themes. These results highlight the importance of transparency, speed, and social sensitivity in crisis communication in the digital era. The study recommends that entertainment agencies respond more strategically to public opinion in order to preserve their reputation in virtual spaces.